2000
DOI: 10.1021/ic0003729
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Studies of Oxomolybdenum Tetrathiolate Complexes:  Origin of Reduction Potential Differences and Relationship to Cysteine−Molybdenum Bonding in Sulfite Oxidase

Abstract: Electronic absorption, magnetic circular dichroism, and resonance Raman spectroscopies have been used to determine the nature of oxomolybdenum-thiolate bonding in (PPh4)[MoO(SPh)4] (SPh = phenylthiolate) and (HNEt3)[MoO(SPh-PhS)2] (SPh-PhS = biphenyl-2,2'-dithiolate). These compounds, like all oxomolybdenum tetraarylthiolate complexes previously reported, display an intense low-energy charge-transfer feature that we have now shown to be comprised of multiple S-->Mo dxy transitions. The integrated intensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
106
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(121 citation statements)
references
References 49 publications
15
106
0
Order By: Relevance
“…These properties are thought to be due, at least to some extent, to the non-planarity of the two attached aromatic groups in those ligands imparting geometric constraints on the complexes with those ligands (for examples see [107] and [108] and references therein). Interestingly, as mentioned here and discussed elsewhere [69], we see only small changes in the structural and spectroscopic measurements as well as reactivity of 1 versus [Mo(O)(SPh) 4 ] ± .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These properties are thought to be due, at least to some extent, to the non-planarity of the two attached aromatic groups in those ligands imparting geometric constraints on the complexes with those ligands (for examples see [107] and [108] and references therein). Interestingly, as mentioned here and discussed elsewhere [69], we see only small changes in the structural and spectroscopic measurements as well as reactivity of 1 versus [Mo(O)(SPh) 4 ] ± .…”
Section: Resultssupporting
confidence: 77%
“…The masses and isotope pattern for the only molybdenum-containing peak in the negative-ion FAB-MS of 1 match the theoretical calculated spectrum for the mononuclear formulation [Mo(O)L 2 ] ± quite well. MCD and RR studies on 1 and [Mo(O)(SPh) 4 ] ± have been performed and compared, and are reported separately [69].…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic voltammogram showed several peaks corresponding to ligand reduction and oxidation, indicating that the ligand exhibits a complex electrochemical behavior because of the presence of electrochemically active thiol and thione groups, consistent with previous reports (Bradbury et al 1981;McNaughton et al 2000;Borsari, Cannio, and Gavioli 2003;Fotouhi et al 2003;Schulzke 2005). The cyclic voltammogram (Figure 1) consisted of three cathodic and anodic peaks, which clearly represented different electrode processes.…”
Section: Electrochemical Properties Of the Ligandsupporting
confidence: 89%
“…A derivatised version of dibenzo [1,2]dithiin has been bound to copper [7] and a molybdenum complex [8] containing two biphenyl dithiolate ligands in a distorted-square-planar-like complex with a molybdenum oxygen triple bond are also known. Mono-and dinuclear nickel complexes have also been reported.…”
Section: Introductionmentioning
confidence: 99%